Implementation of Guidance and Counseling Management in Islamic Educational Institutions - Susanti, Novi; Putri, Nurmila; Asmerat, Desi; Rahmi, Elvi; Septrisia, Reni (Al-Kahfi: Jurnal Pendidikan Agama Islam, 2026)
Guidance and counseling services in Islamic educational institutions are administratively carried out directly by Guidance and Counseling teachers. However, many Islamic educational institutions still implement guidance and counseling management that is not in accordance with the concept of guidance and counseling management. The purpose of this study is to determine how the implementation of guidance and counseling is applied in Islamic educational institutions. This study uses a qualitative method with a case study design approach. Data sources were taken from twenty-three people consisting of one Guidance and Counseling teacher, the principal, the vice principal for student affairs, and twenty students who received guidance and counseling through in-depth interviews selected using purposive sampling techniques. All data were analyzed using the interactive technique of Miles and Huberman. The results of the study indicate that guidance and counseling management is implemented in Islamic educational institutions through the application of management functions, namely; program planning, implementation of guidance and counseling programs in the form of providing services to students, evaluation of guidance and counseling programs, and feedback. The results of this study can be used as initial data for subsequent researchers in examining this problem in different contexts and issues.